Modified sorbents based on natural mineral and its mechanical properties - Kenzhalievich, Kenzhaliyev Bagdaulet; Tatiana, Surkova; Dossymbayeva, Zamzagul; Kairgeldyevna, Koizhanova Aigul; Dinara, Yessimova; Bekzat, Abdikerim (Universitas Negeri Padang, 2024)
The use of modified sorbents based on natural minerals, widely distributed in Kazakhstan, is a promising direction. This direction is related to the development of domestic ion-exchange materials. The republic lacks its own production of synthetic sorbents. The environmental situation in the regions of uranium ore mining and processing is also important. Moreover, the application of synthetic sorbents is not always justified due to their high cost, while the use of natural sorbents is limited by their low sorption capacity. The development of modified ion-exchange materials based on a combination of these is a pressing issue for various industries. Research has been conducted on the choice of modification methods for natural sorbents and the evaluation of their sorption capacity after modification. The modification of natural minerals zeolite and shungite using the